Relationship between the amount of protein intake of DM patients with the healing process of diabetic ulcers at the Ampel Sehat Inpatient Primary Clinic - Naufal Zuhdi Rabbani; Barkah Purwanto; Dyah Suryani; Dewi Yuniasih (Ahmad Dahlan Medical Journal, 2022)
The healing process of diabetic ulcers is influenced by the nutritional status of the patient, especially the nutritional status of the patient's protein intake.  This study was conducted to determine the relationship between the amount of dietary protein intake of DM patients with the healing process of diabetic ulcers at the Ampel Sehat Inpatient Primary Clinic. This study uses a non-experimental quantitative method with a cross-sectional approach, conducted in May - June 2021 with the research subjects being diabetic ulcer patients who underwent treatment, either outpatient or inpatient stay 1 week with the number of subjects 32 patients aged more than 45 years with this type of male and female, patients with type 2 diabetes mellitus, diabetic ulcers in the leg region, the degree of diabetic ulcers according to Wagner with a score of 1-3, and the patient has full consciousness. Data collection on the amount of dietary protein intake of DM patients was obtained through interviews and questionnaires. The data were analyzed by using the chi-square correlation test or Fisher's exact. The research subjects on average did not have sufficient daily protein intake and did not experience the healing process of their diabetic ulcers. The relationship between the amount of dietary protein intake in DM patients and the healing process of diabetic ulcers was found. This study concludes that there is a relationship between the amount of dietary protein intake of DM patients with the healing process of diabetic ulcers at the Ampel Sehat Inpatient Primary Clinic. Abstrak Proses penyembuhan ulkus diabetikum dipengaruhi oleh status gizi pasien, terutama status gizi asupan protein pasien. Penelitian ini dilakukan untuk mengetahui hubungan antara jumlah asupan protein diet pasien DM dengan proses penyembuhan ulkus diabetikum di Klinik Pratama Rawat Inap Ampel Sehat. Penelitian ini menggunakan metode kuantitatif non eksperimental dengan pendekatan cross sectional, dilakukan pada bulan Mei – Juni 2021. dengan subjek penelitian adalah pasien ulkus diabetikum yang menjalani pengobatan, baik rawat jalan maupun rawat inap 1 minggu dengan jumlah subjek 32 pasien berusia lebih. dari 45 tahun dengan tipe ini pria dan wanita, pasien diabetes mellitus tipe 2, ulkus diabetik di daerah kaki, derajat ulkus diabetik menurut Wagner dengan skor 1-3, dan pasien memiliki kesadaran penuh. Pengumpulan data jumlah asupan protein diet pasien DM diperoleh melalui wawancara dan kuesioner. Analisis data menggunakan uji korelasi chi-square atau Fisher's exact. Subyek penelitian rata-rata tidak memiliki asupan protein harian yang cukup dan tidak mengalami proses penyembuhan ulkus diabetikumnya. Ditemukan hubungan antara jumlah asupan protein diet pada pasien DM dengan proses penyembuhan ulkus diabetikum. Penelitian ini menyimpulkan bahwa ada hubungan antara jumlah asupan protein diet pasien DM dengan proses penyembuhan ulkus diabetik di Klinik Pratama Rawat Inap Ampel Sehat         This is an open access article under the CC–BY-SA license. _______